Applying Programmable Logic Control (PLC) for Control Motors, Blower and Heater in the Rubber Drying Processing - Hendra, Hendra; S, Pebriyanto; Hernadewita, Hernadewita; Hermiyetti, Hermiyetti; Yoserizal, Yoserizal (Universitas Ahmad Dahlan, 2021)
Rubber is the largest commodity in Indonesia. Rubber is traditionally processed and dried using bamboo hangers, manual arrangement of bamboo drying rubber, heat from firewood for drying chambers and large areas. This drying process has disadvantages, namely inconsistent drying time, non-uniform room temperature, unequal product quality, and unfriendly drying process. The solution is to overcome the automatic rubber dryer machine that is made using PLC to get the motor operating system for automatic rubber handling in the drying chamber, fixed drying temperature, small drying area, and fast-drying time. The experimental method is used for the automatic rubber drying process with PLC to control the movement of rubber in/out of the chamber dryer, heater, and blower for distribution temperature and other components. From the test results, it is found that the control system can work well at the voltage of each component of 220V, such as a sensor with a current of 0.21A and a stop time of 0.01s-0.3 seconds. The motor, heater, and blower are active (ON) at 220V with a current of 8.27A. The heater requires a current of 1.99A for active (ON) and an active blower (ON) with a current of 0.75A.